Analisis SWOT Sebagai Strategi Meningkatkan Daya Saing - Mashuri Mashuri; Dwi Nurjannah (LPPM ISNJ Bengkalis, 2020)
This research aims to find out how the SWOT analysis as a strategy to improve competitiveness and obstacles in the Bank of Riau Kepri, Pekanbaru Business Unit. The research method used is quantitative descriptive method. The SWOT analysis used is descriptive analysis methods, SWOT matrix and SWOT diagram analysis. Data collection techniques in this study were interviews, questionnaires and literature. The results of this study are the SWOT analysis as a strategy to increase competitiveness needs to be evaluated again so that the formation of good performance from within and from outside the Bank of Riau Kepri, Pekanbaru Sharia Business Unit in advancing these banks throughout Province of Riau and Riau Islands.